Comparative Genomic Insights into Bacterial Induction of Larval Settlement and Metamorphosis in the Upside-Down Jellyfish Cassiopea - Aki Ohdera; Khushboo Attarwala; Victoria Wu; Rubain Henry; Henry Laird; Dietrich K. Hofmann; William K. Fitt; Mónica Medina (mSphere, 2023)
ABSTRACT Bacteria are important mediators of the larval transition from pelagic to benthic environments for marine organisms. Bacteria can therefore dictate species distribution and success of an individual. Despite the importance of marine bacteria to animal ecology, the identity of inductive microbes for many invertebrates are unknown. Here, we report the first successful isolation of bacteria from natural substrates capable of inducing settlement and metamorphosis of the planula larvae stage of a true jellyfish, the upside-down jellyfish Cassiopea xamachana. Inductive bacteria belonged to multiple phyla, with various capacity to induce settlement and metamorphosis. The most inductive isolates belonged to the genus Pseudoalteromonas, a marine bacterium known to induce the pelago-benthic transition in other marine invertebrates. In sequencing the genome of the isolated Pseudoalteromonas and a semiinductive Vibrio, we found biosynthetic pathways previously implicated in larval settlement were absent in Cassiopea inducing taxa. We instead identified other candidate biosynthetic gene clusters involved in larval metamorphosis. These findings could provide hints to the ecological success of C. xamachana compared to sympatric congeneric species within mangrove environments and provide avenues to investigate the evolution of animal-microbe interactions. IMPORTANCE The pelagic to benthic transition for the larvae of many marine invertebrate species are thought to be triggered by microbial cues. The microbial species and exact cue that initiates this transition remains unknown for many animals. Here, we identify two bacterial species, a Pseudoalteromonas and a Vibrio, isolated from natural substrate that induce settlement and metamorphosis of the upside-down jellyfish Cassiopea xamachana. Genomic sequencing revealed both isolates lacked genes known to induce the life history transition in other marine invertebrates. Instead, we identified other gene clusters that may be important for jellyfish settlement and metamorphosis. This study is the first step to identifying the bacterial cue for C. xamachana, an ecologically important species to coastal ecosystems and an emerging model system. Understanding the bacterial cues provides insight into marine invertebrate ecology and evolution of animal-microbe interactions.